Studi Komparasi Penggunaan Base Isolation Tipe Lead Rubber Bearing dan Friction Pendulum Bearing pada Bangunan Gedung Anutapura Medical Center Palu - Suzzan, Amelynda Oktaviyana; Tavio, Tavio (Jurnal Aplikasi Teknik Sipil, 2024)
Earthquake-resistant-building with seismic isolation system is the concept that separate upper building from the source of vibrations on subgrade. Because it's separated, the height of the building is limited to avoid rollout. AMC building is located in Palu City, an earthquake-prone area, so it’s necessary to plan isolation system to reduce the earthquake load and minimalize damage. This study used ETABS program to model structure with fixed-base, LRB and FPB. They are analyzed by pushover and nonlinear time history analyses. The results show that the performance level of fixed-base structure is LS while performance level of LRB and FPB types are IO. The LRB type structure increases the structure period by 129.6%, while the FPB type increases by 160.3% compared to the fixed-base type. The LRB type reduces the roof maximum-drift by 65.6%, while the FPB type reduces by 68.8% compared to the fixed-base roof maximum-drift.